(untitled) (AYUSHDHARA, 2025)
Ayurveda is new hope for the world. It is important to correlate modern science and Ayurveda. According to metabolism of Ayurveda Mamsa dhatu is nourished by the Rakta Dhatu. To decide any parameter of Mamsa Sarata of an individual we should focus on the Rasa and Rakt Dhatu. Through examination of blood or serum we can get any modern parameter to conclude Sarata of Mamsa Dhatu. Sarata Parikshan is the important physical and functional examination of the body. According to Bruhtrayee Heen, Mdhyam and Uttama sarata are seen. To calculate the Mamsa Sarata of person we can use serum protein levels in blood. So it may be useful to develop some parameter while assessing Mamsa Sarata of the individuals. This article is an effort to correlate the Sarata Parikshan with modern science.